Determination of financial performance and transfer pricing aggressiveness: Analysis of sales growth, leverage, company size and intangible assets (literature review) - Supriyadi, Supriyadi; Widyastuti, Tri; Darmansyah, Darmansyah (Educoretax, 2024)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the Determination of Financial Performance and Transfer Pricing Aggressiveness: Analysis of Sales Growth, Leverage, Company Size and Intangible Assets, A Study of the Transfer Pricing Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are that: 1) The Effect of Sales Growth on Financial Performance; 2) The Effect of Leverage on Financial Performance; 3) Effect of Company Size on Financial Performance; 4) The Effect of Intangible Assets on Financial Performance; 5) The Influence of Sales Growth on Transfer Pricing Aggressiveness; 6) The Influence of Leverage on Transfer Pricing Aggressiveness; 7) The Influence of Company Size on Transfer Pricing Aggressiveness; 8) The Influence of Intangible Assets on Transfer Pricing Aggressiveness; and 9) The Influence of Financial Performance on Transfer Pricing Aggressiveness.